Transport Matters 2019
DOI: 10.1332/policypress/9781447329558.003.0015
|View full text |Cite
|
Sign up to set email alerts
|

Will the ‘smart mobility’ revolution matter?

Abstract: Powerful claims are being made about revolution in the transport sector, with digital technology seen as underpinning a new ‘ecosystem’ of more efficient, more pleasant and less environmentally-damaging mobility. The chapter examines how far such claims are based on evidence, and the contextual conditions that would be necessary for such benefits to be realised. The four key technological shifts identified as part of the transition are interrogated: automation, electrification, digitally-enabled mobility, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…The former has been observed by Liu et al [48], who found that females are less likely to pay for AVs than males and that they showed lower acceptance of new technology than men. The latter has been previously confirmed, for example, through a revealed preference study using shared mini-vans (colectivos) in Mexico City [39]. Both issues have also been highlighted through the TOMNET study in four metropolitan areas in the US [64].…”
Section: Literature Reviewmentioning
confidence: 70%
See 1 more Smart Citation
“…The former has been observed by Liu et al [48], who found that females are less likely to pay for AVs than males and that they showed lower acceptance of new technology than men. The latter has been previously confirmed, for example, through a revealed preference study using shared mini-vans (colectivos) in Mexico City [39]. Both issues have also been highlighted through the TOMNET study in four metropolitan areas in the US [64].…”
Section: Literature Reviewmentioning
confidence: 70%
“…Studies to date [36,37] have tended to examine gender differences as a single sociodemographic variable in datasets through hypothetical Willingness-To-Accept/Willingness-To-Pay (WTA/WTP) [36] or actual experience of SAV use [38] rather than gender being the primary variable in framing the study. Other studies which have used existing vehicles (e.g., passenger mini-vans) to test user attitudes towards sharing in the Global South [39] have reported that personal security is a significant factor for female respondents who often feel less comfortable travelling in the same vehicle with strangers, which may be an important factor in SAV usage. In this context, it is pertinent to test gender differences linked with trip-chaining, which is commonly observed in journeys by women.…”
Section: Introductionmentioning
confidence: 99%